PENYEDIAAN AIR SIAP MINUM PADA SITUASI TANGGAP DARURAT BENCANA ALAM (Belajar Dari Kasus Gempa Bumi Yogyakarta Dan Jawa Tengah) - Indriatmoko, Robertus Haryoto; Widayat, Wahyu (Center for Environmental Technology, 2007)
A response in an emergency condition Ã‚Â is the most critical thing in natural disaster. In this situation, every thing is in a panic. Any decision must be taken Ã‚Â tactically, quickly and property to minimize the number victims and severity as the impact of disaster. One of the response in an emergency is to provide facility of drinking water treatment unit which has to be located at the respective disaster area. This unit is designed compacly with high mobility, flexible and easily operated to fullfil the potable water need for the victims. The treatment processes use are filtration, adsorbtion and sterilization. The capacity is 1 M3/hour. Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Katakunci : Tanggap darurat, air minum, ultra filtrasi,Ã‚Â bencana alam, mobilitas tinggi, tepat sasaran, emergency use, potable water treatment.